Insight into the mechanisms and consequences of recurrent telomere capture associated with a sub-telomeric deletion - Santos, Alexsandro dos; Campagnari, Francine; Victorino Krepischi, Ana Cristina; Ribeiro Camara, Maria de Lourdes [UNESP]; Arruda Brasil, Rita de Cassia E. de [UNESP]; Vieira, Ligia; Vianna-Morgante, Angela M.; Otto, Paulo A.; Pearson, Peter L.; Rosenberg, Carla (Springer, 2018)
A complex mosaicism of the short arm of chromosome 1 detected by SNP microarray analysis is described in a patient presenting a 4-Mb 1p36 terminal deletion and associated phenotypic features. The array pattern of chromosome 1p displayed an intriguing increase in divergence of the SNP heterozygote frequency from the expected 50% from the centromere towards the 1p36 breakpoint. This suggests that various overlapping segments of UPD were derived by somatic recombination between the 1p homologues. The most likely explanation was the occurrence of a series of events initiated in either a gamete or an early embryonic cell division involving a 1pter deletion rapidly followed by multiple telomere captures, resulting in additive, stepped increases in frequency of homozygosity towards the telomere. The largest segment involved the entire 1p, and at least four other capture events were observed, indicating that at least five independent telomere captures occurred in separate cell lineages. The determination of breakpoint position by detection of abrupt changes in B-allele frequency using a moving window analysis demonstrated that they were identical in blood and saliva, the tissues available for analysis. We developed a model to explain the interaction of parameters determining the mosaic clones and concluded that, while number, size, and position of telomere captures were important initiating determinants, variation in individual clone frequencies was the main contributor to mosaic differences between tissues. All previous reports of telomere capture have been restricted to single events. Other cases involving multiple telomere capture probably exist but require investigation by SNP microarrays for their detection.
Keywords: telomere capture; UPD; mosaicism; SNP microarray